Examining the association between social class and religiosity: A study of a selected village in Bangladesh - Faiyaz Ahmad; Md. Roknuzzaman Siddiky (Universitas Airlangga, 2026)
Religion is a basic social institution. However, the level of religiosity may vary among people based on social class. Nonetheless, the availability of empirical studies regarding this issue is far from satisfactory. Hence, the study aimed to examine whether social class is associated with religiosity among the people. The study mainly employed a cross-sectional survey design where data were collected at one point in time from a total of 110 participants through face-to-face interview. The samples were drawn based on judgmental sampling from the Muslim inhabitants aged 21 and above of the village Bataiya of Kabirhat Upazila of Noakhali District, Bangladesh. Moreover, three participants were interviewed in-depth in order to substantiate quantitative findings and gain a better understanding of the views of the participants as to how social class influenced religiosity. Religiosity was measured in terms of three dimensions: religious beliefs, religious values, and religious practices. Each dimension involved a set of factors. Gamma coefficients were used to find out the association between religiosity and social class. The study found that each of the factors pertaining to religious beliefs, religious values, and religious practices was negatively associated with social class. All these associations were statistically significant at 95% confidence level (p < 0.05). Hence, the study claimed that social class negatively affects religiosity. In other words, religiosity decreases as social class increases.